2018
DOI: 10.1097/j.pain.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learned analysis of the association of next-generation sequencing–based human TRPV1 and TRPA1 genotypes with the sensitivity to heat stimuli and topically applied capsaicin

Abstract: Supplemental Digital Content is Available in the Text.Machine-learning methods associated next generation–based genotypes with the response to hypersensitization to heat induced by topical application of capsaicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 84 publications
(112 reference statements)
1
23
0
Order By: Relevance
“…The analytical protocol for NGS-based genotype vs phenotype association has recently been established in similarly sized cohorts carrying or not carrying a pain-related phenotype. 63 An overview of the data analysis is shown in ½F1 Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The analytical protocol for NGS-based genotype vs phenotype association has recently been established in similarly sized cohorts carrying or not carrying a pain-related phenotype. 63 An overview of the data analysis is shown in ½F1 Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…117 Two different commercial NGS platforms are currently widely used for diagnostic purposes: the MiSeq/HiSeq/ NextSeq (Illumina, Hayward, CA) and the IonTorrent PGM (Life Technologies, Carlsbad, CA). Although both platforms differ in the technical implementation of NGS, 63,64 multiple studies have shown that both NGS platforms provide reliable sequencing results in routine clinical diagnostics. 22,94,128…”
Section: Next-generation Sequencingmentioning
confidence: 99%
See 3 more Smart Citations